Contract and regulation : a handbook on new methods of law making in private law - Van Gestel, R. A. J. van, 1966-; Brownsword, Roger; Micklitz, Hans-Wolfgang, 1949- (Handbooks of research methods in law series, 2017)
Contract law is increasingly used to serve regulatory purposes considered beyond the reach of private law. This Handbook explores a range of modern practices that are not typically treated in standard expositions of this area. By exploring these phenomena, it reveals the changing role of regulatory private law in a globalised legal world - one where distinctions between public and private law, hard law and soft law, and rule making and contracting have become increasingly blurred. Contributors explore key examples drawing on an extensive range of private law. The book pays close attention to the use of codes of conduct to coordinate and steer behaviour in business-to-business and business-to-consumer relationships, concerning health and safety, environment, and employment conditions. It also examines the formation of contractual 'networks', such as franchises, to regulate multi-party trade relationships, and the application of contracts and contract law to secure business and consumer compliance with public standards. With its global reach and detailed research, this Handbook will appeal to academics exploring the potential of new law making methods and practitioners looking to gain insight into emerging approaches to private law.